A World without Nuclear Power - Ranny Emilia (Andalas Journal of International Studies (AJIS))
Many people believe a distinct feature of markets is the self-assurance. International system, if not the major, particularly accept this pattern. Communication action obviously plays important role in shaping this pattern. For political leaders who primarily concern with economic growth, the operations in market are used as information to the expanding capital and secure civil industry across national boundaries. Nuclear materials and nuclear weapons are also used to the protection as well as to ensure economies continue growing. The Asian youth leaders can set their own agendas to create substantial change in this area. The process is currently moving. Religious nationalism of the youth is part of this process. However a meaningful change can lose itself unless a significant numbers of the youth give priority to human and humanity objectives. With human intelligence as the major tool the youth can make a difference to the world.  To ensure this the primary units should have capabilities to instinctively understand greatest resources for human wisdom based on multiculturalism and inclusiveness. It can begin from creating security culture among the youth based on its potential historically and locally then share the values to communities in their environment.